Nurse managers’ perceptions of care environment supporting older people’s ability to function in nursing homes - Suhonen R.; Karppinen T.; Rodrigues-Martin B.; Stolt M. (Blackwell Publishing Ltd, 2022)
Aim: To describe nurse managers' perceptions of the care environment in nursing homes and how the residents' ability to function may be improved.
Background: The care environment, considered under physical, social and symbolic dimensions, can be used to maintain and enhance the residents' ability to function.
Methods: An exploratory, descriptive qualitative research design based on focus groups (n = 4) was used. Fourteen nurse managers from six nursing homes in Southern Finland participated during 2014. Data were analysed using content analysis.
Results: The physical environment enables self-management, by facilitating a cosy, home-like and aesthetically pleasing environment and by the design of internal structures and assistive devices. The social environment was described as enabling by providing both private and communal spaces, encouraging personal privacy and self-determination whilst supporting communal interaction and involvement. The symbolic environment was described as supporting a personal culture, care culture development and connecting the components of care perspectives in the community including nursing principles, recognizing and accepting variation in approaches to care.
Conclusions: Development in the care environment requires more innovative approaches especially in the social and symbolic dimensions.
Implications for nursing management: The results provide a framework for nurse managers for analysing and developing the care environment supporting residents' ability to function.